2011
DOI: 10.1364/oe.19.005528
|View full text |Cite
|
Sign up to set email alerts
|

Lasing from colloidal InP/ZnS quantum dots

Abstract: High-quality InP/ZnS core-shell nanocrystal quantum dots (NQDs) were synthesized as a heavy-metal-free alternative to the gain media of cadmium-based colloidal nanoparticles. Upon UV excitation, amplified spontaneous emission (ASE) and optical gain were observed, for the first time, in close-packed InP/ZnS core-shell NQDs. The ASE wavelength can be selected by tailoring the nanocrystal size over a broad range of the spectrum. Moreover, the optical gain profile of InP/ZnS NQDs was matched to the second order fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…The structure was characterized by the VSL method and revealed narrow laser peaks (FWHM < 1 nm) when the pump fluency was higher than 5.5 mJ/cm 2 . A DFB structure was also chosen to demonstrate lasing with a close packed film of InP/ZnS QDs (emission at 600 nm) deposited on the grating [66]. The film presented lasing when it was optically pumped above 2 mJ/cm 2 under femtosecond excitation.…”
Section: Lasingmentioning
confidence: 99%
“…The structure was characterized by the VSL method and revealed narrow laser peaks (FWHM < 1 nm) when the pump fluency was higher than 5.5 mJ/cm 2 . A DFB structure was also chosen to demonstrate lasing with a close packed film of InP/ZnS QDs (emission at 600 nm) deposited on the grating [66]. The film presented lasing when it was optically pumped above 2 mJ/cm 2 under femtosecond excitation.…”
Section: Lasingmentioning
confidence: 99%
“…Due to their outstanding properties, including resistance to photobleaching, high quantum yields, superior photostability, bioconjugation capabilities, QDs have been applied in many research fields [1][2][3][4][5]. In biomedical field, QDs have been used as fluorescent tags in biomarkers and fluorescent probes in biomolecule detections [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…12 Therefore, the previous reported InP QDs always possessed broad size distribution and low emission efficiency, and the optical studies of InP QDs were mostly limited within the linear part. 9,13 Recently, by employing noncoordinating solvent and capping InP with ZnS shell of optimized thickness, high-quality InP/ZnS core-shell QDs were synthesized with a narrow size distribution and high emission quantum yield (QY) comparable to CdSe QDs. 14 In this letter, we present our investigation of the optical nonlinearity on these QDs, and it is shown that the colloidal InP/ZnS QDs exhibit strong SA in near resonant regime and significant TPA in nonresonant regime indicating they are of great interest as nonlinear optical materials.…”
mentioning
confidence: 99%